Unification of Theories: a Challenge for Computing Science - Hoare, Tony and (Springer-Verlag, 1999)
Unification of theories is the long-standing goal of the natural sciences; and modern physics offers a spectacular paradigm of its achievement. The structure of modern mathematics has also been determined by its great unifying theories-topology, algebra, and the like. The same ideals and goals are shared by researchers and students of theoretical computing science.